Efectos de la humedad del suelo, del potasio y del nitrógeno sobre la absorción y el crecimiento de Coffea arabica L. - Tesha, A.J; Kumar, D (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Absorption of NPK by potted coffee seedlings was studied at different soil moistures and in relation to the application levels of these minerals. Various growth components wete also measured. Absorption of N and K was not affected upto 50% field capacity but at the lower soil moisture regime it was retarded. Phosphorus absorption was not lowered even at the lowest soil moisture tested in the present work. Nitrogen and potassium showed a positive interaction whereas a negative interaction was observed between N and P. Absorption was fairly well related to the amount of mineral applied. Nitrogen increased extension growth, leaf area as well as the node number. Potassium produced similar effects on the first two but not on the node number. Compensatory growth was noted after the plants, originally maintained at low soil moisture, were amply watered. Nitrogen appeared to act additively in exhibiting compensatory growth. Practical implications of this work are mentioned.